Atmospheric aerosol growth rates at different background station types - Holubová Šmejkalová, Adéla; Zíková, Naděžda; Ždímal, Vladimír; Plachá, Helena; Bitter, Miroslav (Environmental science and pollution research international, 2021)
Highly time-resolved particle number size distributions (PNSDs) were evaluated during 5 years (2013-2017) at four background stations in the Czech Republic located in different types of environments-urban background (Ústí nad Labem), industrial background (Lom), agricultural background (National Atmospheric Observatory Košetice), and suburban background (Prague-Suchdol). The PNSD data was used for new particle formation event determination as well as growth rate (GR) and condensation sink (CS) calculations. The differences or similarities of these parameters were evaluated from perspectives of the different pollution load, meteorological condition, and regional or long-range transport. The median growth rate (4 nm h-1) is very similar at all stations, and the most frequent length of growth lasted between 2 and 4 h. Condensation sink reflects the pollution load at the individual station and their connection to the environment type. The highest median, CS = 1.34 × 10-2 s-1, was recorded at the urban station (Ústí nad Labem), and the lowest (CS = 0.85 × 10-2 s-1) was recorded at the agricultural station (National Atmospheric Observatory Košetice). Conditional probability function polar plots illustrate the influence of source location to GR. These primary potential emission sources involve traffic, operation of a power plant, and domestic heating.
Keywords: Česká republika; Background station; Source location estimation; znečištění ovzduší; New particle formation; Aerosols; aerosoly; Air Pollution; Pollution load; látky znečišťující vzduch; Air Pollutants; Czech Republic; Growth rate; Particulate Matter; Condensation sink; Environmental Monitoring; monitorování životního prostředí; pevné částice